A avaliação da política de formação continuada de professores da rede pública municipal de Fortaleza pós-pandemia da Covid-19: implicações na prática pedagógica - Sousa, Rosimeyre Rodrigues de (2024)
The continuous professional development of teachers in Fortaleza's municipal network is a municipal public policy ensured by Ordinance No. 204/2014. This policy reaffirms the importance of teachers' work by promoting continuous training programs aimed at professional enhancement, recognition, and the improvement of the quality of municipal education. However, the COVID-19 pandemic in 2020 significantly impacted the teaching-learning process in schools. This study aims to evaluate the post-pandemic Continuous Professional Development policy for teachers in Fortaleza, focusing on classroom practices from the perspectives of trainers and teachers. The investigation is grounded in an in-depth evaluation approach, considering the dimensions of content, context, trajectory, and territoriality of the policy. The study adopts a qualitative approach, with exploratory and descriptive objectives, and employs a case study method. The research is conducted in two elementary schools (early years) in District 5 of Fortaleza. Methodological procedures include a bibliographic analysis of scientific literature, laws, decrees, documents, and field research with interviews and non-participant observation in the two schools. The results highlight the importance of continuous professional development in pedagogical transformation, while also emphasizing the need to align strategies with the real demands of teachers and students. Notably, there is a discrepancy between the guidelines proposed in training documents and their practical implementation, with socio-emotional challenges significantly influencing classroom practices. Additionally, the study reveals that some teachers' resistance to change can significantly hinder the effectiveness of the continuous professional development strategies. This research contributes to reflections on educational policies and pedagogical practices that better address the needs of students and teachers in a rapidly changing and complex context